Synthesis and characterization of a pi-conjugate, covalent layered network derived from condensation polymerization of the 4,4 '-bipyridine-cyanuric chloride couple - Bourlinos, A.B.; Dallas, P.; Sanakis, Y; Stamopoulos, D.; Trapalis, C; Niarchos, D. (EUROPEAN POLYMER JOURNAL, 2006)
Nucleophilic substitutions of the reactive chlorine atoms in cyanuric chloride by the bridging 4,4'-bipyridine in refluxing toluene lead to quaternarization of the latter and the subsequent formation of a pi-conjugate, covalent layered network. The network is composed of central 1,3,5-triazine units with 4,4'-bipyridinium rings covalently attached and balanced by the released chloride ions. Due to the extremely high electron deficiency of the triazine rings, the material undergoes partial reduction by its compensated chloride ions resulting in a radical concentration of 1 X 1020 spin g(-1), according to EPR quantitative analysis. In this instance, the radicals provide stability to the organic network by minimizing its electron deficiency. The material exhibits thermal and electrochemical stability, as evidenced by thermal gravimetric analysis (TGA) and cyclic voltammetry techniques. As such, the pi-conjugate organic material displays low band gaps and electrical conductivity in the range of 10(-4)-10(-5) S cm(-1) at room temperature. (c) 2006 Elsevier Ltd. All rights reserved.